The beam transport system in the SRS-1200 - Ivashchenko, V.E.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2002)
In NSC KIPT the synchrotron radiation source SRS-1200 for the Ukrainian national synchrotron center (Kiev) is developed. An injector for a storage ring is the electron linear accelerator with energy 180 MeV. For compactness of a complex LUE-180 dispose under a storage ring. The transport system provides transport of electron beam from linear accelerator without losses and injection him in the storage ring. The calculations of the performances of transport systems with five-lens and three-lens variants of translation line, and also with use 42 and 45-th of degree rectangular and sector bending magnets were carried out. As a result of the comparative analysis the five-lens symmetric variant of translation line with 42-th degree sector bending magnets was chosen. In the report the basic results of calculations, parameters and performances of transport system of electron beam are submitted.